Dependence of the phosphate sorption capacity on the aluminium and iron in Finnish soils - Kaila, Armi (Agricultural and Food Science, 1963)
An attempt was made to study to what extent the capacity of the more or less acid soils in Finland to sorb phosphate may be explained on the basis of their content of aluminium and iron. The indicator of the phosphate sorption capacity was calculated on the basis of the Freundlich adsorption isotherm according to the procedure proposed by TERÄSVUORI (8). The material consisted of 390 samples from cultivated and virgin soils representing both topsoils and subsoils. The indicator of the phosphate sorption capacity, the coefficient k, varied in the present material from 40 to 1510. The mean values (with the confidence limits at the 95 per cent level) were for the 109 samples of sand and fine sand soils 290 ± 17, for the 103 samples of loam and silt soils 201 ± 24, for the 151 clay soils 308 ± 20, and for the 27 humus soils 236 ± 41. The total linear correlation coefficients between k and the soil pH, and its contents of organic carbon or clay were low or negligible in most of the soil groups. The correlation of k with the content of aluminium extracted by Tamm’s acid ammonium oxalate was fairly close in the clay soils (r = 0.84***), lower in the sand and fine sand soils (r = 0.77***), and in the loam and silt soils, and in the humus soils it was rather poor (r = 0.65*** and 0.63*** resp.). The elimination of the effect of the ammonium oxalate soluble iron decreased the correlation in the two latter groups quite markedly (to 0.32** and 0.37 resp.), while the corresponding decrease in the coefficients for the former groups was less significant (to 0.64*** and 0.75*** resp.). The elimination of the effect of the ammonium oxalate soluble aluminium, on the other hand, decreased the correlation coefficients between k and the ammonium oxalate soluble iron in the sand and fine sand soils from 0.59*** to 0.26**, in the loam and silt soils from 0.73*** to 0.54***, in the clay soils from 0.70*** to 0.51***, and in the humus soils from 0.68*** to 0.49*. The part of variation in k which could be explained on the basis of the variation in the contents of aluminium and iron was different in the different kind of soils. According to the coefficients of determination and the coefficients of multiple determination, the variance in the aluminium content determined 59 per cent of the variance in k in the sand and fine sand soils and 70 per cent in the clay soils; considering also the content of iron increased this part to 61 per cent and 78 per cent, resp. In the loam and silt soils the variation in the iron content explained 53 per cent of the variation in k, in the humus soils this percentage was 47. Considering both aluminium and iron, the proportion of the variance in k which could be explained in these two groups was increased to 60 per cent and 54 per cent, resp. Thus, in addition to the contents of ammonium oxalate soluble iron and aluminium, other factors must be found to explain the variation in the phosphate sorption capacity, particularly in other soil groups than in the clay soils. The soil pH and its content of organic carbon obviously play only a minor role among these ctors.